THE SLOVENIAN REGULATION ON MOUNTAIN TRAILS - Gawrysiak-Zabłocka, Aleksandra (Zeszyty Prawnicze, 2022)
2022 marks the centenary of the institution of the Knafelc Blaze (Svn. Knafelčeva markacija), one of the symbols of Slovenian mountaineering. This is a good opportunity to take a look at current Slovenian regulations regarding hiking trails. The Slovenian Mountain Paths (Trails) Act (Svn. Zakon o planinskih poteh) covers many aspects of the subject, such as the construction, maintenance and marking of mountain paths and the conditions for their safe use. This regulation can be an interesting contribution to the discussion which has been going on for many years in Poland, on the need for, and way to regulate issues relating to hiking trails.